Learning Revolution with Student Worksheets Based on Bondowoso Local Wisdom for Fourth Grade of Elementary School - Suhartiningsih; Adita Dwi Safirah; Yuni Fitriyah Ningsih; Nasution (Universitas Pendidikan Ganesha, 2024)
Local wisdom is essential to introduce to students, but only a few schools can introduce local wisdom from the local area and integrate it into learning material. The teaching materials used by teachers also do not contain material based on local wisdom. This impacts students who need to learn the local wisdom of the area where they live, and their learning outcomes decrease. This research aims to test the validity, effectiveness, and practicality of Bondowoso's local wisdom-based LKPD to improve student learning outcomes. This type of research is development research. The model used to develop products is the Borg and Gall model. The subjects of this research were class IV students. Data collection methods use observation techniques, interviews, questionnaires and learning outcomes tests. Data analysis techniques use product validation, t-test, relative effectiveness test, student response, and practicality test. The validation results carried out by 4 validators achieved a score of 94.75 in the very feasible category. The relative effectiveness test result was 43.43% with the medium effectiveness category. The results of calculating student responses scored 97.67 in the very effective category. The practicality test by the observers received a score of 94.25 in the convenient category. It was concluded that the LKPD based on Bondowoso local wisdom was valid, effective and practical for use in learning.